Administrative Challenges to the Integration of Oral Health With Primary Care: A SWOT Analysis of Health Care Executives at Federally Qualified Health Centers. Issue 3 (July 2017) - Norwood, Connor W.; Maxey, Hannah L.; Randolph, Courtney; Gano, Laura; Kochhar, Komal
Abstract : Inadequate access to preventive oral health services contributes to oral health disparities and is a major public health concern in the United States. Federally Qualified Health Centers play a critical role in improving access to care for populations affected by oral health disparities but face a number of administrative challenges associated with implementation of oral health integration models. We conducted a SWOT (strengths, weaknesses, opportunities, and threats) analysis with health care executives to identify strengths, weaknesses, opportunities, and threats of successful oral health integration in Federally Qualified Health Centers. Four themes were identified: (1) culture of health care organizations; (2) operations and administration; (3) finance; and (4) workforce. Abstract : Supplemental Digital Content is Available in the Text.